STRATEGI PENINGKATAN INDEKS PEMBANGUNAN MANUSIA (IPM) DI KOTA CILEGON - Setiawan, Alwin (Jurnal Kebijakan Pembangunan Daerah, 2025)
The gap in human development achievements between regions in Banten Province indicates the need for special strategies for areas like Cilegon City to accelerate the improvement of the Human Development Index (HDI). This research aims to analyze the Human Development Index (HDI) achievement of Cilegon City, evaluate its constituent components, identify influencing factors, and formulate strategies for HDI improvement based on SWOT analysis. The HDI achievement of Cilegon City in 2024 is 78.83, categorized as "high," but it has not yet reached the "very high" level like some other cities in this province. Analysis of the HDI dimensions shows that the standard of living (per capita expenditure) has the highest contribution, followed by health (life expectancy), while the education dimension, particularly the expected years of schooling, remains the main challenge. The inhibiting factors include disparities in access to basic services between regions, the low quality of educators and healthcare providers, and minimal cross-sector synergy. Through SWOT analysis, the WO (Weakness–Opportunities) strategy is considered the most relevant because it emphasizes strengthening local capacity and utilizing external partnership opportunities. With an integrated, participatory, and data-driven approach, it is hoped that the improvement of Cilegon City's HDI can occur sustainably and equitably.